If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 6 + 5x + -12 = x + 6 + 7x + -48 Reorder the terms: 6 + -12 + X + 5x = x + 6 + 7x + -48 Combine like terms: 6 + -12 = -6 -6 + X + 5x = x + 6 + 7x + -48 Reorder the terms: -6 + X + 5x = 6 + -48 + x + 7x Combine like terms: 6 + -48 = -42 -6 + X + 5x = -42 + x + 7x Combine like terms: x + 7x = 8x -6 + X + 5x = -42 + 8x Solving -6 + X + 5x = -42 + 8x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '6' to each side of the equation. -6 + X + 6 + 5x = -42 + 6 + 8x Reorder the terms: -6 + 6 + X + 5x = -42 + 6 + 8x Combine like terms: -6 + 6 = 0 0 + X + 5x = -42 + 6 + 8x X + 5x = -42 + 6 + 8x Combine like terms: -42 + 6 = -36 X + 5x = -36 + 8x Add '-5x' to each side of the equation. X + 5x + -5x = -36 + 8x + -5x Combine like terms: 5x + -5x = 0 X + 0 = -36 + 8x + -5x X = -36 + 8x + -5x Combine like terms: 8x + -5x = 3x X = -36 + 3x Simplifying X = -36 + 3x
| 8v-36=-2v+4 | | 42-3w=4w | | 45+(x-7)=90 | | 6x=5000 | | a=25(.15)10 | | n/3-8=12 | | 2+-8=-24 | | 4(3x+11)=37(16+4x) | | 4(3x+11)=2.9(16+4x) | | 35-6u=u | | 4(3x+11)=2.6(16+4x) | | -f(x)=x^2+5x-2 | | 4(3x+11)=2.7(16+4x) | | 4(3x+11)=0(16+4x) | | 4(3x+11)=2.5(16+4x) | | 9-7v-1.1-8v= | | y=-x^2+5x+14 | | 2m+8-7m=23 | | .0833(156x-17)=5(18+12x) | | 9a-20= | | Cos^2x-5sinx-5=0 | | f(x)=-163+200x | | 12-w=52 | | 10x-14.30=26.00 | | 3(2m+4)=6m+12 | | H+28.80=86.40 | | x(.97)=275 | | H(x)=6x+2 | | H+1=28.80 | | (-2x^3+x)+(3x-6)= | | 3y+6=5y+2 | | 2-m/2 |